Tournaisian and Viséan Lophophyllum of Gorskiy (1932) from the Kirghiz Steppe and a possible ancestor of a new Bashkirian rugose coral genus from the Donets Basin (Ukraine) - Fedorowski, Jerzy (Geologos, 2017)
All specimens assigned by Gorskiy (1932) to the genus Lophophyllum Milne Edwards and Haime, 1850 are revised, redescribed and reillustrated. The corallite identified by him as a second, specifically indeterminate species of Lophophyllum is here questionably included in Amygdalophyllum Dun and Benson, 1920. For the reminding specimens two new, unnamed genera are suggested. ”Lophophyllum” subtortuosum Gorskiy, 1932 belongs to a new, non-dissepimented genus of an unknown family. A possible relationship between gen. nov. 1, sp. nov. 1 and the new Bashkirian genus from the Donets Basin (Ukraine) is proposed.